The Analysis of Mental and Physical Structure of Dawn Poetry: “Time Celebrated Rooster’s Crowing” - Herman Wijaya; Lalu Mas’ud; Moh. Irfan (ppjbsip, 2020)
The purpose of this study is to describe the inner and physical structure of the poem